2021
DOI: 10.1021/acsnano.1c09176
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Separation of Plasmonic Hot-Electron Generation and a Hydrodehalogenation Reaction Center Using a DNA Wire

Abstract: Using hot charge carriers far from a plasmonic nanoparticle surface is very attractive for many applications in catalysis and nanomedicine and will lead to a better understanding of plasmon-induced processes, such as hot-charge-carrier- or heat-driven chemical reactions. Herein we show that DNA is able to transfer hot electrons generated by a silver nanoparticle over several nanometers to drive a chemical reaction in a molecule nonadsorbed on the surface. For this we use 8-bromo-adenosine introduced in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 64 publications
(137 reference statements)
2
21
0
Order By: Relevance
“…Thus, we believe that through Ca 2+ bridging the adsorption of Br‐Ade on Ag surface, Br‐Ade shifts from physisorption to chemisorption, facilitating the direct electron transfer from the surface plasmon resonance modes of Ag nanostructures to Br‐Ade acceptor orbitals, characteristic of CID. Therefore, the increase in the dehalogenation rate of Br‐Ade following the addition of Ca 2+ is assigned by us to CID (i.e., direct electron transfer transitions), whereas in the lack of Ca 2+ ions, the dehalogenation reaction is likely driven by Landau damping, as indicated in previous studies [ 29 ] (i.e., hot electrons). By the same token, thermal effects can be disregarded since the addition of Ca 2+ ions would not influence in any way the temperature of the AgNW upon laser irradiation.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, we believe that through Ca 2+ bridging the adsorption of Br‐Ade on Ag surface, Br‐Ade shifts from physisorption to chemisorption, facilitating the direct electron transfer from the surface plasmon resonance modes of Ag nanostructures to Br‐Ade acceptor orbitals, characteristic of CID. Therefore, the increase in the dehalogenation rate of Br‐Ade following the addition of Ca 2+ is assigned by us to CID (i.e., direct electron transfer transitions), whereas in the lack of Ca 2+ ions, the dehalogenation reaction is likely driven by Landau damping, as indicated in previous studies [ 29 ] (i.e., hot electrons). By the same token, thermal effects can be disregarded since the addition of Ca 2+ ions would not influence in any way the temperature of the AgNW upon laser irradiation.…”
Section: Resultsmentioning
confidence: 54%
“…As far as we know, the way in which specific ion effects impact plasmonassisted reaction rates has never been studied before. The dehalogenation of Br-Ade to Ade has been studied extensively by the Bald group [29][30][31][32][33][34] and, importantly, a thermal-driven reaction has been excluded through power-dependent measurements as well as in studies using nanosecond laser pulses, suggesting that the main electron transfer pathway from AgNPs to Br-Ade is a plasmon-assisted one. This is also confirmed by a recent study using in situ electrochemical SERS.…”
Section: Introductionmentioning
confidence: 99%
“… 53 , 59 To determine the decomposition of BrTP, the intensity of the ring stretching vibration at 1076 cm –1 is plotted as a function of time (see Figure 6 c) and exemplary fitted with second-order fractal kinetics. 37 , 43 To exclude the effects of spectral overlaps of the 1076 cm –1 peak with the signals from possible reactions products, the intensities of the less intense peaks at 302 and 507 cm –1 are plotted as well, which show the same decomposition kinetics (see Figure S6 ). As illumination time increases, the SERS signal of BrTP seems to converge to a residual intensity, which is already observed previously for reactions on plasmonic substrates 33 35 but not in the simulations described above.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated previously that chemical hotspots, areas with high reactivity, correlate with optical hotspots, namely, areas with high electric field enhancement . Therefore, SERS is a widely used technique to study light-induced reactions on plasmonic substrates, since the reactions can be triggered and tracked simultaneously and the reaction products can be identified. However, the inhomogeneous distribution of hotspots on the nanoscale typically hampers the quantitative analysis of the reaction by SERS, as a large proportion of the signal originates from the hotspots with high reactivity and hardly any signal from areas with low reactivity is observed. Moreover, it raises the question of whether reaction parameters like reaction constant and order can be still extracted from the SERS measurements and how the overall chemical conversion of reactants on the NP surface is disguised by the plasmonic enhancement . To date, several studies have been published that deal with different approaches that consider the inhomogeneity of the plasmonic substrate to deal with the kinetics in plasmon-driven reactions monitored by SERS. One approach is fractal-like kinetics, which is typically applicable to systems with limited mobility of the reactants, leading to a time dependency of the reaction rates. , , On the other hand, including an offset into the reactant signal intensities, which reflects a residual intensity after long reaction times, allows us to fit the SERS data with standard reaction kinetics equally well, even though the origin of this residual intensity still remains speculative. , …”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that even though the kinetics curves obtained through SERS experiments carry little information about the reaction order, they are still very useful to compare the different properties of the studied materials. [44][45][46] Here, we fitted the curves using a second-order fractal reaction kinetics equation:…”
Section: Plasmon-induced Crosslinking Reactionmentioning
confidence: 99%